Diversification's effect on firm value - Berger, Philip G.; Ofek, Eli (Journal of Financial Economics, 1995)
We estimate diversification's effect on firm value by imputing stand-alone values for individual business segments. Comparing the sum of these stand-alone values to the firm's actual value implies a 13% to 15% average value loss from diversification during 1986–1991. The value loss is smaller when the segments of the diversified firm are in the same two-digit SIC code. We find that overinvestment and cross-subsidization contribute to the value loss. The loss is reduced modestly by tax benefits of diversification.